Modification of The Spectrophotometric Analysis Protocol by Sims D. and Gamon to Analyze Leaf Pigment Content using Green Spinach (Amaranthus hybridus) as a Model Plant - Yudiansyah, Yudiansyah; Ismiyanti, Ismiyanti; Aziz, Sandra Arifin (Journal of Tropical Crop Science, 2024)
The analysis of pigment content in plants, particularly chlorophyll a, chlorophyll b, anthocyanin, and carotenoids, is crucial to assess their physiological performance. The spectrophotometry method by Sims and Gamon offers practicality and reliable results. This research established several variables to achieve more precise results. Green spinach leaf samples were used as a model to analyze their pigment content, determining the minimum sample area or weight, the maximum limit that does not violate Beer’s law, and the temperature during analysis. The limit of quantitation (LoQ) is the smallest quantity of analytes in a sample that still meets the criteria for accuracy and precision in testing. The research results show that using a leaf punch with a diameter of 9 mm approaches the LoQ value. To avoid measurements nearing the LoQ limit, it is advisable to use leaf punch diameters of 10- or 12-mm. Leaf punches of 22 mm are still safe to use, as there has been no deviationfrom Beer’s law. Using unchilled acetone at 27°C did not show significant differences compared to using cold acetone at 7°C for the content of chlorophyll a, total chlorophyll, and carotenoids. However, for chlorophyll b and anthocyanin, despite significant differences, the chlorophyll content measured at room temperature was more practical and relatively higher compared to cold acetone, thus disproving concerns about pigment damage.